External aluminium supply regulates photosynthesis and carbon partitioning in the Al-accumulating tropical shrub Melastoma malabathricum - Ali, Sajid; Mahmud, Khairil; Weitz, Hedda; H. Kritzler, Ully; Burslem, David F. R. P. (Public Library of Science, 2024)
Aluminium (Al) is toxic to most plants, but recent research has suggested that Al addition may stimulate growth and nutrient uptake in some species capable of accumulating high tissue Al concentrations. The physiological basis of this growth response is unknown, but it may be associated with processes linked to the regulation of carbon assimilation and partitioning by Al supply. To test alternative hypotheses for the physiological mechanism explaining this response, we examined the effects of increasing Al concentrations in the growth medium on tissue nutrient concentrations and carbon assimilation in two populations of the Al-accumulator Melastoma malabathricum. Compared to seedlings grown in a control nutrient solution containing no Al, mean rates of photosynthesis and respiration increased by 46% and 27%, respectively, total non-structural carbohydrate concentrations increased by 45%, and lignin concentration in roots decreased by 26% when seedlings were grown in a nutrient solution containing 2.0 mM Al. The concentrations of P, Ca and Mg in leaves and stems increased by 31%, 22%, and 26%, respectively, in response to an increase in nutrient solution Al concentration from 0 to 2.0 mM. Elemental concentrations in roots increased for P (114%), Mg (61%) and K (5%) in response to this increase in Al concentration in the nutrient solution. Plants derived from an inherently faster-growing population had a greater relative increase in final dry mass, net photosynthetic and respiration rates and total non-structural carbohydrate concentrations in response to higher external Al supply. We conclude that growth stimulation by Al supply is associated with increases in photosynthetic and respiration rates and enhanced production of non-structural carbohydrates that are differentially allocated to roots, as well as stimulation of nutrient uptake. These responses suggest that internal carbon assimilation is up-regulated to provide the necessary resources of non-structural carbohydrates for uptake, transport and storage of Al in Melastoma malabathricum. This physiological mechanism has only been recorded previously in one other plant species, Camellia sinensis, which last shared a common ancestor with M. malabathricum more than 120 million years ago.